Retromer in Synaptic Function and Pathology - Brodin, Lennart; Shupliakov, Oleg (Frontiers in Synaptic Neuroscience, 2018)
The retromer complex mediates export of select transmembrane proteins from endosomes to the trans-Golgi network or to the plasma membrane. Dysfunction of retromer has been linked with slowly progressing neurodegenerative disorders, including Alzheimer´s and Parkinson´s diseases. As these disorders affect synapses it is of key importance to clarify the function of retromer-dependent protein trafficking pathways in pre- and postsynaptic compartments. Here we discuss recent insights into the roles of retromer in the trafficking of synaptic vesicle proteins, neurotransmitter receptors, and other synaptic proteins. We also consider evidence that implies synapses as sites of early pathology in neurodegenerative disorders, pointing to a possible role of synaptic retromer dysfunction in the initiation of disease.